Loss of beaver dams decreases floodplain connectivity in Colorado headwater streams - Schultz, Kayla, author; Morrison, Ryan, advisor; Rathburn, Sara, committee member; Nelson, Peter, committee member (Colorado State University. Libraries, 2025)
As ecosystem engineers, beavers (Castor canadensis) modify river corridor form through dam building on lower order, low-gradient streams. The numerous geomorphic, ecological, and hydrological impacts of beaver dams are well documented, primarily through observations of active beaver systems. When beavers are removed from a system, their unmaintained dams wash out, altering the stream's hydrologic regime. The assumption that beaver dams increase floodplain connectivity is frequently presumed but has not been directly quantified. Moreover, many contemporary river restoration techniques aim to restore natural functions historically provided by beavers without fully understanding the hydrological benefits of past beaver activity. To address this knowledge gap, I quantified the change in floodplain connectivity caused by the loss of beaver dams at three headwater tributary sites in the Kawuneeche Valley, Rocky Mountain National Park, Colorado, USA. I developed two-dimensional steady-state hydraulic models to compare metrics of floodplain connectivity under historical (beaver-active) and present (no beaver activity) scenarios. The historical scenarios featured modeled beaver dams matching conditions in the year 1990 when beavers were present in the landscape. I simulated three low-to-moderate recurrence interval flood discharges to assess floodplain connectivity metrics, including the volume of water on the floodplain, the fraction of flow moving through the floodplain, the volumetric flux into the floodplain, and mean site and floodplain residence times. I found that the loss of beaver dams decreases floodplain connectivity across all connectivity metrics (up to a 96.5% loss in connectivity) except mean floodplain residence time, which increased in the absence of dams. Channel velocities also increased following the loss of beaver dams. Results from the sensitivity analysis show that the flow state and condition of the beaver dam, modeled here by the parameters porosity and drag coefficient, can have reach-scale impacts on floodplain connectivity. Notably, while I observed floodplain disconnection at each site, the magnitude of change varied depending on both site-specific characteristics (local topography, human impacts, etc.) and on the flood magnitude. I conclude that, in headwater streams, beaver dams play an important and quantifiable role in facilitating floodplain connectivity, and floodplain disconnection from the loss of dams has major implications for other ecological and geomorphic floodplain processes. Understanding the degree and variability to which beaver dams historically promoted floodplain connectivity is especially timely considering the increasing interest in beaver-related restoration.
Keywords: floodplain connectivity; restoration; hydraulic modeling; beaver dams